Advanced Maternal Age Impairs Myelination in Offspring Rats - Han, Wei; Pan, Ya'nan; Han, Ziyao; Cheng, Li; Jiang, Li (Frontiers in Pediatrics, 2022)
The effects of advanced maternal age (AMA) on the neurodevelopment of offspring are becoming increasingly important. Myelination is an important aspect of brain development; however, few studies have focused on the effects of advanced pregnancy on myelin formation in offspring. This study aims to evaluate the association between AMA and myelin sheath development in offspring. We studied the expression of myelin basic protein (MBP) in the immature offspring of 3- and 12-month-old Sprague–Dawley female rats at different time points (7 d, 14 d, 28 d and 60 d) after birth with immunofluorescence and western blot. The myelin sheath ultrastructure was observed with transmission electron microscopy in immature and mature offspring. Extracellular signal-regulated kinase 1 and 2 (ERK1/2) and phosphorylated ERK1/2 (p-ERK1/2) were detected by western blot in immature offspring at the above time points.The MBP expression level gradually increased with postnatal development in the offspring of both the AMA and Control (Ctl) groups, but the MBP level in the offspring of the AMA group was lower than that of the Ctl group at 7 and 14 d after birth. In addition, the ultrastructure of the myelin sheath was impaired in AMA offspring during the early postnatal period; however, the myelin sheath was not significantly affected in offspring during adulthood. ERK phosphorylation generally increased after birth in both the AMA and Ctl groups. However, ERK phosphorylation during the early postnatal period was lower in AMA offspring than in Ctl offspring. Interestingly, ERK phosphorylation during early adulthood was higher in AMA offspring than in Ctl offspring. The peak ERK phosphorylation in the AMA group was abnormal and delayed. Our results indicated that AMA is associated with poor developmental myelin formation in offspring. The ERK signaling pathway may play an essential role in the mechanism underlying the adverse effects of AMA on myelin sheath development in offspring.